PENERAPAN BUDAYA PERUSAHAAN DALAM PEMBENTUKAN CITRA PERUSAHAAN JASA PERHOTELAN - Sunuantari, Manik (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2012)
There are so many factors that influence customer imageof a building hotel. One of thefactors that stand out in image formation of a hotel is culture. It is reflected in the behavior, norms, standard values that was adopted, philosophy, rules and communication climate in a hotel.The theory that applied in this research is from Heskett by using constructivism approach. The research location is Hotel Sentral and Hotel Sofyan Betawi, where prior they shared same values. Later, they became apart due to differences in values, segments. But because there was various difference, so they were decided to separated, and grow up appropriate with the wishes of their founder. Based on the research result, and comparison study, it is indicated that each hotel has different characteristics corporate culture, segments, and corporate image. The condusive communication climate allows the formation of a good corporate image. For instance, employees have an opportunity to share and learn with each other. Open communication will effect good culture formation and absorb by all members of the company. Hotel Sentral applied an adaptive culture due to the dynamism of changes in customer’s needs and wants. In the other hand, Hotel Sofyanembrased on more static approach, due to the obedience to the founder. Customer’s image of Hotel Sentral is not favourable, because the issue with the local community which resulting the lack of social responsibility. The while in Hotel Sofyan’s images is favourable in the mind of the customers, due to it is positive relationship with the community and this resulting customers stay are convenient. Keywords: corporate culture, corporate image, norm, value and communication climate.